A select library of the Nicene and Post-Nicene Fathers of the Christian church - Schaff, Philip; Wace, Henry; Jerome, St (Edinburgh, Scotland T and T Clark, 1889)
Includes bibliographical references and indexes.
V. VI contains letters and select works of St Jerome
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600